Students' Tips for Enhancing Writing Skills using Social Media in Pandemic Era - Rosalina, Elsa; Nasrullah; Umar, Vebrianti; Pitria Ningsih, Rahma (Universitas Pendidikan Ganesha, 2022)
Writing is one of the skills in language learning. Writing is also the most difficult skill for language learners because when the students start writing, they must collect the idea from their brain and then type or write it into a good paragraph. Social media and daily life cannot be separated today. Social media has evolved into the most important online platform for connecting people. This research tries to analyses the contribution of social media in improving students' writing skills. This research used the qualitative method because it was to describe students' tips to enhance writing skills using social media. The participants of this research were 2 students from English Language Education Study Program Batch 2019. They were students D and T. They were chosen because they got the highest score in the